Influence of skeletal class, occlusal pattern, age and sex on facial soft tissue thickness: a retrospective study using cone beam computed tomography in a Brazilian population - Fernanda Silvestre; Lilian Cristina Vessoni Iwaki; Fernanda Vessoni Iwaki; Wilton Mitsunari Takeshita; Mariliani Chicarelli da Silva (Acta Scientiarum. Health Sciences)
This retrospective study analyzed the influence of skeletal class, occlusal pattern, age, and gender on the thickness of facial soft tissues, utilizing cone-beam computed tomography (CBCT) in a Brazilian population. In a retrospective approach, 239 CBCT scans were examined, including 100 male and 139 female patients, categorized into skeletal and occlusal classes (I, II, and III). The soft tissue thickness was evaluated at 10 strategic points along the midline. Significant differences were detected related to skeletal classes, gender, and age. In the occlusal classes, there were significant variations between genders, particularly evident in classes I and II, and less so in class III. Age was found to be an influential factor, especially in individuals under 40 years of age, with notable differences in class I. This study highlights that skeletal class, occlusal pattern, gender, and age play fundamental roles in determining facial soft tissue thickness. These findings are important for improving the accuracy of facial reconstructions and are particularly relevant for the Brazilian population.